Research and Application of the Synergistic Support System of “LDAGF” in an Extremely Soft and Fragile Fully Mechanized Caving Face Roadway - Xianjie Ni; Yuan Yuan; Xinzhu Hua; Ke Ding (Applied Sciences)
This study aims to alleviate the serious deformation of surrounding rock (SR) in an extremely soft and fragile fully mechanized caving face roadway (ESFFMCFR, the 8# coal seam, Huaibei mining area) under a conventional support. Laboratory tests of roadway SR were conducted. The results show that in this coal seam, the extremely soft and fragile coal body has a high clay mineral content, so it is of low strength and breaks and softens easily. With reference to the mechanical tests on coal and rock mass around the coal seam and the monitoring results of roadway deformation, the roadway deformation is mainly caused by the development of fractures in the roadway SR, the separation of the support body and SR and the loose supporting structure. Considering the engineering environment and deformation characteristics of SR in the ESFFMCFR (the 8# coal seam, Huaibei mining area), this study proposed a synergistic support system of “lowering, drilling, anchoring, grouting and flatting (LDAGF)” for the ESFFMCFR based on the synergistic mechanism of support and SR under the basic principles of synergetics. Specifically, the synergistic support system of “LDAGF” includes the following measures: floor breaking and side lowering, bolt advance support, anchor cable support, advance water injection and grouting and flat-roof U-shaped steel shed support. Furthermore, this synergistic support system was applied on the ESFFMCFR in the 8# coal seam of Xinhu and Guobei coal mines, Huaibei mining area. The on-site application results reveal that when the synergistic support system is adopted, the maximum subsidence values in the above roadway roofs are 117 mm and 121 mm and the maximum displacement values of the two sides are 66 mm and 74 mm, respectively, which proves an excellent support effect. The synergistic support system, which can effectively control the serious deformation of the SR in ESFFMCFRs and ensure long-term stability and safety of the roadways, is suitable for the support of ESFFMCFRs and is of great guiding significance for roadways of the same type.